Potter’s syndrome: bilateral renal agenesis (a report of two cases emphasizing associated malformations) - Tınaztepe, Keriman; Balcı, Sevim; Tınaztepe, Behçet; Dağlı, Elif (The Turkish Journal of Pediatrics, 1983)
Potter’s syndrome is a combination of bilateral renal agenesis and accompanying facial and nonrenal features. It is a rare disorder and occurs in one in every 2900-4800 deliveries. Over a period of 15 years, two cases of Potter’s syndrome were recorded among 2000 pediatric necropsies performed at Hacettepe Children’s Hospital. Both cases presented had facial, skin and genital abnormalities. The second one showed anal atresia as well. Both babies died within the first ten hours after admission. The nonrenal features of the syndrome are thought to be secondary to oligohydramnios, but there are some features that cannot be explained by uterine compression.